Membrane Filter Technique for Enumeration of Enterococci in Marine Waters - Levin, M. A. (1975)
A membrane filter procedure is described for the enumeration of enterococci in marine waters. The procedure utilizes a highly selective and somewhat differential primary isolation medium followed by an in situ substrate test for identifying colonies of those organisms capable of hydrolyzing esculin. The procedure (mE) was evaluated with known streptococci strains and field samples with regard to its accuracy, sensitivity, selectivity, specificity, precision, and comparability to existing methods. Essentially quantitative recovery was obtained with seawater-stressed cells of Streptococcus faecalis and S. faccium. Neither S. bovis, S. equinus, S. mitis, nor S. salivarius grew on the medium. The selectivity of the medium was such that a 10,000-fold reduction in background organisms was obtained relative to a medium which contained no inhibitors and was incubated at 35 C. About 90% of those typical colonies designated as enterococci confirmed as such and about 12% of the colonies not so designated were, in fact, identified as enterococci. Plate to plate variability across samples approximated that expected by chance alone. Verified recoveries of enterococci from natural samples by the mE procedure, on the average, exceeded those by the KF method by one order of magnitude.